Examination malpractices: an indisciplinary act towards a societal ruin, causes, agents, control and the way forward - S. Adiaha, Monday; U. Ocheje, David (International Journal of Scientific World, 2017)
Examination Malpractices as an indisciplinary act towards a societal ruin was surveyed. Findings of this study presented examination malpractices as an act capable of dragging the society into ruin. Results of the statistical analysis were significant (p<0.005), proofing examination malpractices as an act been perpetrated in schools for the benefit of the parties involved. Different forms, causes and agents of examination malpractices have been identified, seeking a control guide where these factors can be tackled for the benefit of the Nigerian society and the world at large. The mode of life contrary to societal development has been identified as indiscipline with characteristics, which do not conform to the development of the environment. The regular violations of school rules, constant violence been experienced in the country today, turn-down of court orders, broken homes, including loss of respect for Humanity, metamorphoses from indiscipline, from one stage/form to the other. The Research finding further revealed that this act is one of the possible reasons for some level of underdevelopment been experienced in some of the developing countries like Nigeria. Tackling indisciplinary acts like examination malpractice can help to revive a society’s morals, including her economic status, where development can be sustainable for the benefit of the present and unborn generations, and to create an ideal society where human dignity and respect for academics as one of the factors for strong economic development can prevail. Recommendations of this survey include good home training and upbringing, leadership by example, engagement of an individual in life rewarding activities to exit idleness, including setting of realistic rules guiding the act of examination malpractice as an act of indiscipline.